Procrastination among university students of Malaysia and Pakistan - Mohd. Kosnin, Azlina (2014)
Procrastination can be defined as the intentional delay of an important task in the favor of an unimportant and trivial task in order to avoid doing the important task. Delaying the important task usually causes hindrance in its completion and makes the person become less productive than they can otherwise be. (Wolters and Corkin, 2012). Procrastination can be found in many aspects of one’s life and it is quite pervasive phenomenon in terms of its affect on different strata of people. Nonetheless, during the course of this study the focus would be on procrastination that is present in a student of higher education during their studies.